Sahel Atlas of Changing Landscapes: Tracing trends and variations in vegetation cover and soil condition - United Nations Environment Programme (United Nations Environment Programme, 2012)
The atlas provides a pictorial overview of the application of land degradation surveillance a science-based approach to land health monitoring and assessment. Systematic sampling and observation of ground conditions are combined with new technology for rapid soil characterization and with fine to moderate resolution satellite imagery to provide powerful inference about soil, vegetation and socioeconomic conditions at local to regional scales. Investments in regional application of this approach will provide a sound scientific basis for understanding and managing climate-vegetation-management processes and feedbacks in the Sahel and elsewhere.